Silver bullet or millstone? A review of success factors for implementation of marketing automation - Daniel Murphy (Cogent Business & Management, 2018)
With a current market size of more than 11 billion, expected to double within 5 years, more businesses are expected to acquire, implement, and update marketing automation systems in the near future. However, for all the promises of profit and organisational revolution, there is already a gap between those who successfully implement and use marketing automation and those who don't. This paper reviews the small body of literature and publicly available research and reports to determine the key antecedents of marketing automation success. There are seven common factors that businesses should consider and follow pre, during, and post-marketing automation implementation. These include; the availability of the correct human resources and expertise, reviewing and implementing new business processes, correctly scoping the implementation project, gaining organisational buy-in, creating customer-centric content, continuing investment, and the setting of realistic expectations.
Keywords: 650